Sport : a biological, philosophical, and cultural perspective - Schulkin, Jay (Columbia University Press, 2016)
From the Olympians of ancient Greece to today's professional athletes, from adult pick-up soccer games to children's gymnastics classes, people at all levels of ability at all times and in all places have engaged in sport. What drives this phenomenon? In Sport, the neuroscientist Jay Schulkin argues that biology and culture do more than coexist when we play sports, they blend together seamlessly, propelling each other toward greater physical and intellectual achievement. To support this claim, Schulkin surveys history, literature, and art and engages the work of philosophers and the latest psychological and sociological research. He connects sport's basic neural requirements, including spatial and temporal awareness, inference, memory, agency, direction, competitive spirit, and endurance, to the demands of other human activities. He affirms sport's natural role as a creative evolutionary catalyst, turning the external play of sports inward and bringing profound insight to the diversion that defines our species. Sport, we learn, is a fundamental part of human life--Publisher's website.